Analisis Tafsir Surah Al-Baqarah Ayat 275-279 Tentang Riba (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This research aims to analyze the interpretation of Surah Al-Baqarah verses 275–279, which comprehensively discuss the concept of usury (riba) in Islam. These verses emphasize the fundamental distinction between usury and lawful trade, while clearly stating the prohibition of riba as an economic practice that leads to injustice and exploitation. This study employs a qualitative method with a library research approach, using primary sources such as the Qur’an, classical and contemporary tafsir books, and other relevant supporting literature. The findings indicate that riba is viewed as a practice that damages social and economic order because it contradicts the principles of justice, fairness, and mutual assistance. Furthermore, these verses highlight severe warnings for those who persist in usury and call upon believers to repent and abandon any remaining claims derived from riba. This research is expected to contribute to a deeper understanding of the prohibition of riba and its relevance to modern economic systems, particularly in applying Islamic values of justice, ethical responsibility, and social welfare in contemporary society.